KOMUNIKASI INTERPERSONAL ANTARA GURU DENGAN SISWA DALAM KEGIATAN PEMBELAJARAN DI SMK N 1 MUARA BUNGO - Yesi Isnaini Rachmah; Sarmiati Sarmiati; Azwar Azwar (Ensiklopedia of Journal, 2022)
Juvenile delinquency and deviant behavior is a social phenomenon that often occurs in society. From a theoretical point of view, juvenile delinquency is the cause of failure in self-control. They may fail to distinguish between acceptable and unacceptable behavior by the surrounding community. This research uses. qualitative research method with a case study approach. The result of this study is that the communication carried out by the BK teacher in tackling the delinquency of students at SMK N 1 Muara Bungo is very effective between teachers and their students. This interpersonal communication is very helpful as an intermediary in finding problems and finding solutions to a problem that is being faced by the students. Coupled with the classical approach taken by BK teachers in approaching these students in making it easier for them to reduce problems in education. The existence of a social penetration theory can actually be more intimate between students who have problems with the BK teacher. So the final result of this research is that between teachers and students they grow closer to each other along with the ongoing process of intense interpersonal communication.